The Impact of Problem-Based Learning (PBL) Module on Critical Thinking Skills on Electrolyte and Nonelectrolyte Solutions - Sari, Dwivelia Aftika; Herman, Mimi; Putri, Steva Dara; Hidayati, Hidayati (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This research aims to determine the impact of using the Problem-Based Learning (PBL) module on students' critical thinking skills on the material of electrolyte and non-electrolyte solutions. This research uses a quasi-experimental method with a Nonequivalent Control Group Design. Sampling was carried out by using cluster purposive sampling. The data collection technique used was a critical thinking skillsÂ  test instrument in the form of essay questions. Hypothesis testing was carried out by using the independent sample t-test. The result showed that using PBL module on the material of electrolyte and non-electrolyte solutions has a positive impact on the critical thinking skills of students at SMA N 1 Sijunjung and SMA N 7 Sijunjung. This is proven by the results of the t-test analysis using SPSS that the significance value is 0.000 less than 0.05 with a significance level (Î± = 0.05) so that H0 is rejected and H1 is accepted. This means that the use of the PBL module has an impact on students' critical thinking skills regarding the material of electrolyte and non-electrolyte solutions. The critical thinking skills of students in the experimental class who learned using the PBL module were higher than those in the control class in both schools.